Propolis as a local treatment of oral candidiasis in mef users of the dental clinic - Unheval. Huánuco - 2011 - Ballarte Baylón, Antonio (2017)
The intention of this study was to determine the efficiency of the propóleo as a local treatment of candidiasis orally in women in fertile age, to give him scientific support we determine the march fitoquímica qualitative and quantitative of the propóleo, we established the incident, determined the symptoms and signs that predict a better finding of the pathology and classified to the pathology according to Grinspan; in the investigation we use the classic design, cuasi experimentally longitudinally and market, identify the women in fertile age carriers of the oral candidiasis, classify in the sharp phase and then we separate in two groups experimentally and of control, to which we fulfil the pre test We annotate the characteristics of the injury, the experiment was applied and to other one the placebo and after 15 days, we apply the post test, annotate the characteristics of the injury; the findings that we obtained were: that the oral candidiasis in the sharp phase treats itself with the hackneyed application of propoleo and has four times the probability of recovering, her comparing with the group control, the oral candidiasis during the year 2011 In women in fertile age they were 60 new patients, the symptoms that predict better the finding of candidiasis orally, were an ardor in 62 % and pain in 18 %, and the sign blush in 12 %; her classifying in the sharp phase to 40 patients who did 67 %; concluding that the hackneyed application of the propoleo like local treatment in candidiasis oral in women in fertile age is effective.